2018
DOI: 10.1002/etep.2574
|View full text |Cite
|
Sign up to set email alerts
|

A study of the effect of power electronic system interaction with power system voltage stability

Abstract: Summary Voltage stability has of recent been a subject of growing concern to power system utilities. In this paper, 2 techniques, one based on topological structure of power networks and the other on the conventional power flow solution, are proposed for voltage stability analysis. The network structural characteristics theory participation factor proposed is formulated to identify the weak bus of the system. The voltage stability enhancement is achieved through the incorporation of power electronic–based thyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 33 publications
(95 reference statements)
0
6
0
Order By: Relevance
“…In this regard, these indicators may seem to be a proper tool for voltage stability assessment. Nevertheless, in the sequel, it will be shown that these indices have a major drawback, which is not considered in the literature . To explain this drawback, consider the simple network shown in Figure A, which includes three transmission lines connected in series.…”
Section: Improved Lsz Indicatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, these indicators may seem to be a proper tool for voltage stability assessment. Nevertheless, in the sequel, it will be shown that these indices have a major drawback, which is not considered in the literature . To explain this drawback, consider the simple network shown in Figure A, which includes three transmission lines connected in series.…”
Section: Improved Lsz Indicatorsmentioning
confidence: 99%
“…Nevertheless, in the sequel, it will be shown that these indices have a major drawback, which is not considered in the literature. 35,[48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65][68][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84] To explain this drawback, consider the simple network shown in Figure 13A, which includes three transmission lines connected in series. In this network, the maximum transferable power is 67 as follows: When P max passes through the transmission corridor, it is expected that the line indices calculated for line 2 (or two other ones) reach to their critical threshold to show the proximity of the operating point to stability boundary.…”
Section: Figure 12mentioning
confidence: 99%
“…13,14 It is worth to reveal that numerous research have been conducted to contribute in better F I G U R E 1 Worldwide installed capacity of PV power understanding of the long-term voltage instability caused by large PV integration. 7,[15][16][17][18][19][20][21] In contrast, very few studies have focused on the short-term voltage stability, which is also known as dynamic voltage stability. [22][23][24][25][26][27][28] In Reference 22, the authors have investigated the impacts of LVRT by PV inverters on the DVS, and concluded that DVI is likely to occur in highly PV penetrated power systems after a severe fault if the PV inverters are incapable of providing the LVRT.…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic voltage stability can be classified either in short‐term (several seconds) or long‐term (seconds to minutes) time period scale 13,14 . It is worth to reveal that numerous research have been conducted to contribute in better understanding of the long‐term voltage instability caused by large PV integration 7,15‐21 . In contrast, very few studies have focused on the short‐term voltage stability, which is also known as dynamic voltage stability 22‐28 .…”
Section: Introductionmentioning
confidence: 99%
“…The authors in [10] proposed two approaches to identify the placement of the FACTS controller of the suitable nodes to ensure voltage stability. The first technique is based on the topological structure of power networks, while the seond technique is based on the conventional power flow [10].…”
Section: Introductionmentioning
confidence: 99%